2022
DOI: 10.1108/jiabr-03-2021-0108
|View full text |Cite
|
Sign up to set email alerts
|

Islamic labelling and corporate governance: a perspective of Shariah compliance firms

Abstract: Purpose Islamic label of an organization attracts Muslims for investment. There is a rising concern with a huge profile of corporate governance related to the Islamic rules (principles). In this context, this study aims to examine the effect of Islamic labelling on corporate governance in the Pakistani setting. Design/methodology/approach This study used a panel data set comprising 120 non-financial Shariah-compliant and non-Shariah-compliant Islamic firms listed on the Pakistan Stock Exchange over the perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…Islamic principles are integral to shaping corporate governance frameworks in Shariah-compliant firms, reflecting a rising concern for governance aligned with Islamic rules (Ullah et al, 2022). Studies have shown that Islamic banks adhere to a significant portion of corporate governance attributes, indicating a commitment to Islamic principles in governance practices (Srairi, 2015).…”
Section: Islamic Ethics Training For Employeesmentioning
confidence: 99%
“…Islamic principles are integral to shaping corporate governance frameworks in Shariah-compliant firms, reflecting a rising concern for governance aligned with Islamic rules (Ullah et al, 2022). Studies have shown that Islamic banks adhere to a significant portion of corporate governance attributes, indicating a commitment to Islamic principles in governance practices (Srairi, 2015).…”
Section: Islamic Ethics Training For Employeesmentioning
confidence: 99%
“…Moral values are at the core of Islamic teachings and are the basis of an ethical governance structure. Therefore, shariah compliance improves the efficacy of CG mechanism and practices in Pakistan (Ullah et al, 2023).…”
Section: Introductionmentioning
confidence: 97%